Diseño y construcción de una desgranadora de maíz con capacidad de 500 kg / día (2023)
This paper proposes the design and construction of a corn sheller with a capacity of 500 kg/day, for the smallholding "LOS LIRIOS" in the rural area of Pore Casanare. The shelling machine will reduce the time required for the shelling process, taking into account that currently this is done manually and/or also with shelling equipment lease, increasing production cost. It will have a shelling mechanism that removes or detaches the grains from the cob, which is powered by an electric or thermal motor. A mechanical power transmission system, a structure that supports the different components, a feeding hopper, a sieve that separates the grains from the cobs and the motor control elements.